Anelídeos poliquetos associados a um briozoário: II. Palmyridae Polychaetous annelids associated to a bryozoan: II. Palmyridae - Eloisa H Morgado; A. Cecília Z Amaral (Brazilian Journal of Oceanography, 1981)
Two species of Palmyridae were found in colonies of the bryozoan Schizoporella unicorns (Johnston): Bhawania brunea new for the science, and Chrysopetalum occidentale Johnson, cited for the first time for the Brazilian coast. These two species are described and their distribution is established. Bhawania brunea sp. nov. is conspicuously characterized by the structures on the prostomium and the configuration of the paleae.